(3GdYbhO GdeSeGI aj GdebGhdI,GdhcGdI,GdcaGdIs - (3YOfGf GHQGgje(B, (3GdSQMGfs ((3YeGf(B:s (3ecJHI OGQ GdKbGaI ddfTQ(B,s, 2001)
(3YbO GdebGhdI(B:(3CQcGf YbO GdebGhdI, BKGQ YbO GdebGhdI, GfJgGA GdebGhdI, YbO GdhcGdI(B:(3CQcGf YbO GdhcGdI ,BKGQ GdhcGdI, GfJgGA GdhcGdI, YbO GdcaGdI(B:(3CQcGf GdcaGdI, BKGQ GdcaGdIs
(3HHdhZQGajG U(B.242s
Keywords: (3GdbGfhf GdeOfjs; (3GdcaGdIs; (3YbhO GdebGhdIs